Booster seat laws and child fatalities: a case–control study. Issue 5 (5th October 2009) - Farmer, P; Howard, A; Rothman, L; Macpherson, A
Abstract : A case–control study examined, primarily, the association between booster seat laws and fatalities among children in frontal collisions and, secondarily, the association between booster seat laws and reported restraint use, and restraint use and child fatalities. Children who died in a crash in the US were cases, and children who survived a fatal crash were controls. Subjects were child passengers (4–8 years old) in the Fatality Analysis Reporting System Database, 1995–2005. In states with a booster seat law, children were less likely to die than in states without a law (OR 0.80; 95% CI 0.66 to 0.98). They were also more likely to be restrained (adjusted OR 1.59; 95% CI 1.21 to 2.09) and were more likely to be correctly restrained (adjusted OR 4.44; 95% CI 3.18 to 6.20). It is concluded that booster seat laws are associated with a decrease in child deaths and an increase in correct restraint use among children involved in a fatal crash in the USA.